Muscarinic acetylcholine receptor down-regulation limits the extent of inhibition of cell cycle progression in Chinese hamster ovary cells. - Detjen, K (1995)
Cellular desensitization is believed to be important for growth control but direct evidence is lacking. In the current study we compared effects of wild-type and down-regulation-resistant mutant m3 muscarinic receptors on Chinese hamster ovary (CHO-K1) cell desensitization, proliferation, and transformation. We found that down-regulation of m3 muscarinic acetylcholine receptors was the principal mechanism of desensitization of receptor-activated inositol phosphate phospholipid hydrolysis in these cells. Activation of wild-type and mutant receptors inhibited anchorage-independent growth as assayed by colony formation in agar. However, the potency for inhibition of anchorage-independent growth was greater for cells expressing the mutant receptor. Activation of either receptor also initially inhibited anchorage-dependent cell proliferation in randomly growing populations. Rates of DNA synthesis and cell division were profoundly reduced by carbachol in cells expressing either receptor at early time points. Analysis of cell cycle parameters indicated that cell cycle progression was inhibited at transitions from G1 to S and G2/M to G1 phases. However, mutant receptor effects on anchorage-dependent growth were sustained, whereas wild-type receptor effects were transient. Thus, receptor down-regulation restored cell cycle progression. In contrast, activation of either receptor blocked entry into the cell cycle from quiescence, and this response was not reduced by receptor down-regulation. Therefore, activation of m3 muscarinic acetylcholine receptors inhibited CHO cell anchorage-dependent and -independent growth. In anchored cells carbachol inhibited the cell cycle at three distinct points. Inhibitions at two of these points were eliminated by wild-type receptor down-regulation while the other was not. These results directly demonstrate that desensitization mechanisms can act as principal determinants of cellular growth responses.